Suppression of flow pulsation activity by relaxation process of additive effect on viscous media transport; IOP Conference Series: Earth and Environmental Science; Vol. 27 : Problems of Geology and Subsurface Development - Kharlamov (Harlamov) S. N. Sergey Nikolaevich; Dedeyev P.; Meucci L.; Shenderova I. V. Inna Vladimirovna; Manastirniy A.; Usenko M. (Latest Technology of Oil-and-Gas Pipelines and Petroleum Storage, 2015)
Title screen